"I'm going to push this door open. You can close it": A qualitative study of the brokering work of oncology clinic nurses in introducing early palliative care. (February 2020) - Mohammed, Shan; Savage, Pamela; Kevork, Nanor; Swami, Nadia; Rodin, Gary; Zimmermann, Camilla
Background: Early palliative care improves quality of life during life-prolonging treatment for patients with cancer, but the role of nurses in facilitating the early involvement of palliative care is unclear. Aim: To conceptualize the psychosocial processes involved in the introduction and provision of palliative care by oncology nurses. Design: A constructivist qualitative grounded theory study was conducted. Setting/participants: A total of 20 nurses (6 staff nurses, 10 nurse practitioners, and 4 advanced practice nurses) completed semi-structured interviews. Participants were from multiple ambulatory care oncology clinics (i.e. breast, pancreatic, hematology) in a comprehensive cancer center. Results: The core category, brokering palliative care, represented the overarching concept of the study that linked other subcategories. The other subcategories were as follows: opening the door —creating the possibility of discussing early palliative care at a time when patients show signs of being receptive to this discussion; building trust —establishing relationships with patients as a starting point for open discussions about palliative care; tackling misconceptions —addressing patients' assumptions about palliative care as signifying death; and advocating with oncologists —seeding the process of referral by bringing patients' concerns forward. Conclusion: Oncology nurses play a central role in "brokering" the introduction of early palliative care; this process is supported by their relational proximity to patients and their location "in between" the patient and the oncologist. Training all nurses in palliative care and empowering them to have proactive discussions in a collaborative practice context would allow greater access to early palliative care.